2011
DOI: 10.5146/tjpath.2011.01074
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting non-sentinel lymph node involvement in sentinel node positive breast carcinoma

Abstract: In patients with invasive breast cancer and positive sentinel node, area percent of sentinel node occupied by tumor, and the number of sentinel nodes removed are independently predictive of non-sentinel node involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(45 reference statements)
1
3
0
2
Order By: Relevance
“…Luminal A-like patients with a high ratio (1/1 or 2/2) had a higher risk of having 4 LNMs. These results are in line with findings from previous studies [26,28,29]. A low SN ratio among patients with one to two positive SNs seems to reliably predict a low axillary tumor burden.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Luminal A-like patients with a high ratio (1/1 or 2/2) had a higher risk of having 4 LNMs. These results are in line with findings from previous studies [26,28,29]. A low SN ratio among patients with one to two positive SNs seems to reliably predict a low axillary tumor burden.…”
Section: Discussionsupporting
confidence: 92%
“…SNB results in a false negative SN in 10% of the cases [22][23][24] and in most cases with a solitary positive SN there are no additional LNMs [25]. Factors that predict tumor engagement of NSNs are the number of positive SNs, 3 SNs removed, macrometastases in SNs, a larger percentage of the SN occupied by metastases, lymphovascular invasion, tumor size, extracapsular growth, higher histologic grade and estrogen receptor negativity [25][26][27]. The SN macrometastasis ratio was predictive of axillary tumor burden in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The results from our study clearly confirm that size of primary tumor (T) presents strong independent predictive factor od SLN positivity in breast cancer patients, which correlates with the results of other similar studies ( 20 ). Some authors investigated the size of metastatic deposits within SLNs and found that both the number of positive SLNs as well as the size of metastatic deposits within SLNs independently serve as predictive factors of other non-SLNs involvement ( 21 ). There are also other studies that further analyze the predictive value of SLN.…”
Section: Discussionmentioning
confidence: 99%
“…SLD pozitif olgularda, NSLD durumunun, metastazların öngörülmesi: Erken evre invaziv meme kanseri hastalarının %40-70'inde SLD de tek metastaz saptanmakta ve bu nedenle gereksiz aksiller diseksiyonu önleyip morbiditeyi azaltmak için aksiller NSLD durumunu, tutulumunu öngören faktörlerin belirlenmesine yönelik çalışmalar yapılmaktadır (52).…”
Section: Sld'nin Pn0-pn1mi Evrelemesinde Ve Raporlandırılmasındakigüçunclassified
“…Meme kanseri ve pozitif SLD olan hastalarda, primer tümör boyutu, peritümöral lenfovasküler invazyon yanısıra SLD'deki metastazın boyutu, metastazların anatomik yerleşimi (subkapsüler, parankimal ya da ikisi birlikte), metastatik SLD sayısı, perikapsüler invazyon, çıkarılan SLD'nin sayısının, NSLD tutulumu açısından önemli bulgular içinde yer aldığı belirtilmektedir (52 (13,32,33,45,52). Bunlar da NSLD'nin durumunu %100 doğrulukla belirlememektedir (33).…”
Section: Sld'nin Pn0-pn1mi Evrelemesinde Ve Raporlandırılmasındakigüçunclassified